Mental imagery in psychiatry: conceptual & clinical implications. (28th January 2019) - Ji, Julie L.; Kavanagh, David J.; Holmes, Emily A.; MacLeod, Colin; Di Simplicio, Martina
Abstract : Mental imagery refers to the experience of perception in the absence of external sensory input. Deficits in the ability to generate mental imagery or to distinguish it from actual sensory perception are linked to neurocognitive conditions such as dementia and schizophrenia, respectively. However, the importance of mental imagery to psychiatry extends beyond neurocognitive impairment. Mental imagery has a stronger link to emotion than verbal-linguistic cognition, serving to maintain and amplify emotional states, with downstream impacts on motivation and behavior. As a result, anomalies in the occurrence of emotion-laden mental imagery has transdiagnostic significance for emotion, motivation, and behavioral dysfunction across mental disorders. This review aims to demonstrate the conceptual and clinical significance of mental imagery in psychiatry through examples of mood and anxiety disorders, self-harm and suicidality, and addiction. We contend that focusing on mental imagery assessment in research and clinical practice can increase our understanding of the cognitive basis of psychopathology in mental disorders, with the potential to drive the development of algorithms to aid treatment decision-making and inform transdiagnostic treatment innovation.